Genomic Insight into the Host–Endosymbiont Relationship of Endozoicomonas montiporae CL-33T with its Coral Host - Ding, Jiun-Yan; Shiu, Jia-Ho; Chen, Wen-Ming; Chiang, Yin-Ru; Tang, Sen-Lin (Frontiers in Microbiology, 2016)
The bacterial genus Endozoicomonas was commonly detected in healthy corals in many coral-associated bacteria studies in the past decade. Although it is likely to be a core member of coral microbiota, little is known about its ecological roles. To decipher potential interactions between bacteria and their coral hosts, we sequenced and investigated the first culturable endozoicomonal bacterium from coral, the E. montiporae CL-33T. Its genome had potential sign of ongoing genome erosion and gene exchange with its host. Testosterone degradation and type III secretion system are commonly present in Endozoicomonas and may have roles to recognize and deliver effectors to their hosts. Moreover, genes of eukaryotic ephrin ligand B2 are present in its genome; presumably, this bacterium could move into coral cells via endocytosis after binding to coral’s Eph receptors. In addition, 7,8-dihydro-8-oxoguanine triphosphatase and isocitrate lyase are possible type III secretion effectors that might help coral to prevent mitochondrial dysfunction and promote gluconeogenesis, especially under stress conditions. Based on all these findings, we inferred that E. montiporae was a facultative endosymbiont that can recognize, translocate, communicate and modulate its coral host.